Kondisi Perekonomian Nusa Tenggara Barat pada Gelaran MotoGP Mandalika dengan Pendekatan Big Data di Sektor Pariwisata - Dewi Krismawati; Satria Bagus Panuntun (Seminar Nasional Official Statistics, 2022)
The COVID-19 pandemic that occurred two years ago was a factor that greatly influenced the economic slowdown, both at the global and national levels. The International Pertamina Grand Prix MotoGP Mandalika was enthusiastically welcomed by the Indonesian people. The existence of the 2022 MotoGP event is an opportunity to encourage economic recovery both at the level of the Province of West Nusa Tenggara (NTB) and nationally. This study aims to see the impact of the Mandalika MotoGP event on the economy, especially the tourism sector in NTB by utilizing Big Data technology. The results of this study indicate a significant increase in community mobility during the event, especially in transit areas and parks. The increase in TPK also occurred quite significantly in March 2022 compared to February 2022. The number of flights to Lombok International Airport increased sharply from 18 to 21 March 2022. Some of these indicators show that the MotoGP mandalika event is a moment for the revival of the NTB economy.